Assessment of the Effectiveness of Energy Transfer for Shore-to-Ship Fast Charging Systems (International Journal of Scientific Research in Science and Technology, 2024)
Charging systems from shore to ship are typically designed based on a range of operational and design parameters, encompassing onboard power and propulsion needs, available charging durations, and the capacity of local power networks. In areas with weak grid infrastructure, onshore energy storage is often employed to facilitate high-power charging for vessels requiring short charging intervals. Nevertheless, incorporating on-shore energy storage adds complexity to the system, and the selection of system configuration can profoundly affect the efficiency of energy transfer from the grid to the vessel. This study presents a comparative analysis of energy efficiency among AC, DC, and Inductive shore-to-ship charging solutions for short-distance ferries utilizing both AC and DC-based propulsion systems. Findings illustrate that an increased reliance on onshore battery power correlates with decreased overall energy efficiency during the charging process. Thus, optimizing energy efficiency necessitates careful consideration when distributing the load between the grid and onshore battery. Results indicate that DC charging offers advantages over other solutions for AC-based propulsion systems in terms of energy efficiency. However, for DC-based propulsion systems, the most efficient solution may be either DC or AC charging, contingent upon the distribution of load between the grid and onshore battery. Furthermore, it is inferred that despite adding additional conversion stages and complexity to the system, the energy efficiency of inductive charging is comparable to wired schemes. Considering the added benefits of contactless charging, such as reliability, safety, and robustness, these findings advocate for the adoption of inductive charging as a promising solution.